3‐D base force element method on meso‐damage analysis for recycled concrete. (12th May 2021) - Ying, Liping; Peng, Yijiang; Kamel, Mahmoud M. A.
Abstract: The 3‐D base force element method (BFEM) for damage problems is proposed, which is applied to analyze the damage mechanism of recycled aggregate concrete (RAC). A piecewise curve damage constitutive model is given to simulate the constitutive relationships of RAC phases. A spatial random aggregate model of RAC is proposed. 3‐D numerical simulations of RAC under uniaxial mechanical stress are carried out. The macroscopic stress–strain relationship and failure process of RAC under uniaxial stress based on the 3‐D BFEM are obtained. The numerical results show a good consistency with the experimental results. This illustrates that the numerical simulation can reflect the nonlinearity deformation, stress redistribution, and crack propagation process of RAC. In addition, the influence of recycled aggregate replacement percentage on strength and elastic modulus is investigated. The results show that the content proportion of recycled aggregate has a great effect on RAC, which have to be considered in the analysis and the application of RAC.